Omics technologies : tools for food science - Benkeblia, Noureddine (Boca Raton, FL : CRC Press, 2012)
"Examining the application of genomic information and high-throughput profiling technologies as tools for the nutrition and food science industries, this book takes a particular interest in the transformation from industrial to sustained food technologies and the role of these omics tools to mitigate the growing pressure of limited natural resources and environmental degradation. Providing detailed descriptions right down to the molecular level, it discusses the prominence of diet and food components as prime environmental factors that affect the genome, transcriptome, proteome, and metabolome and how these delicate interactions define individual health or disease"--Provided by publisher
1. Nutrition science and "Omics" technologies:ethical aspects in global health -- 2. Array platform for food safety and quality -- 3. Metabolomics and food science:concepts and serviceability in plant foods and nutrition -- 4. Foodomics:a new omics for a new food era -- 5. Proteomics in food biotechnology -- 6. Challenges in feasible problem construction in nutritional genomics:an empirical study -- 7. Genomics and breeding in food crops -- 8. Genomics of fruit quality and disorders -- 9. Systems biology approaches reveal new insights into the molecular mechanisms regulating flesh fruit quality -- 10. Coffee Genomics -- 11. Omics approaches to meat quality management -- 12. Functional genomics to improve meat quality in pigs -- 13. Meat science and proteomics -- 14. Wine-omics:new platforms for the improvement of yeast strains and wine quality -- 15. Aspergillus flavus genetics and genomics in solving mycotoxin contamination of food and feed
Includes bibliographical references (p. 388-402) and index
Keywords: Sustainability; Biotechnology; Food Technology; Food; Genomics; Nutritional Physiological Phenomena